2014
DOI: 10.1016/j.socscimed.2014.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Does more equitable governance lead to more equitable health care? A case study based on the implementation of health reform in Aboriginal health Australia

Abstract: There is growing evidence that providing increased voice to vulnerable or disenfranchised populations is important to improving health equity. In this paper we will examine the engagement of Aboriginal community members and community controlled organisations in local governance reforms associated with the Aboriginal Health National Partnership Agreements (AHNPA) in Australia and its impact on the uptake of health assessments. The sample included qualitative and quantitative responses from 188 people involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…Following an analysis of the links between health assessment uptake and Indigenous community and organisational engagement in health reforms, Kelaher et al . () concluded that ‘stronger links between Indigenous organisations and between mainstream organisations working with Indigenous organisations’ can improve engagement with the health system and therefore, health equity. However, improvements at the operational level within tertiary health care are largely lacking (Dwyer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Following an analysis of the links between health assessment uptake and Indigenous community and organisational engagement in health reforms, Kelaher et al . () concluded that ‘stronger links between Indigenous organisations and between mainstream organisations working with Indigenous organisations’ can improve engagement with the health system and therefore, health equity. However, improvements at the operational level within tertiary health care are largely lacking (Dwyer et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Kelaher et al. ) . For these potentials to be realised, however, Indigenous organisations need a range of capabilities in governance.…”
Section: Introductionmentioning
confidence: 98%
“…The majority of studies ( n = 13) in this review were case studies. The remaining studies included quantitative design (Bloom et al., ; Chandra et al., ; Geist, ; Glik et al., ; Goytia et al., ; Patterson et al., ); qualitative design (Boutain & McNees, ; Burkhalter et al., ; Collignon, Men, & Tan, ; Honeycutt et al., ; Johnson et al., ; Radermacher, Karunarathna, Grace, & Feldman, ; Taras et al., ); systematic review (Frew et al., ); and mixed‐method design (Houston et al., ; Kakietek et al., ; Kelaher et al., ; Laborde, Brannock, Breland‐Noble, & Parrish, ; Riehman et al., ).…”
Section: Resultsmentioning
confidence: 99%